KAJIAN YURIDIS PRAKTIK PERSEKONGKOLAN DALAM TENDER (Studi Putusan KPPU Perkara Nomor 24/KPPU-I/2016) - Intania Az Zarah (Jurnal Privat Law, 2023)
This research aims to determine the consideration of a conspiracy in the Commission decision on Case No. 24 / KPPU-I / 2016 and implementation of legal justice in the Commission’s Decision Case No. 24 / KPPU-I / 2016 in terms of economic and fairness aspects. This research is a normative law research which are prescriptive and applied. The approach used are the statute approach and the case approach. The sources of legal materials consist of primary legal materials, secondary and tertiary legal materials with literature study. This research used deductive analysis technique. Commission’s in Decision Number 24 / KPPU-I / 2016 has considered on the case in accordance with Law No. 5 of 1999, however its considerations do not consider whether the consequences of the conspiracy are hindering business competition or not. The commission in deciding the Commission Case Number 24 / KPPU-I / 2016 tended to only pay attention to the justice aspect  while the economic aspect seemed a little neglected, so that the KPPU Decision Number 24 / KPPU-I / 2016 did not fully fulfill legal justice.Keywords: Tender Conspiracy; Business Competition; Fairness